Secret fling with the king - Meier, Susan (Harlequin romance, 2025)
Jessica was delighted with her promotion to King Mateo Stepanov's personal assistant. But the unexpected sparks she feels with her gorgeous boss are a different thrill entirely! Though the guarded widower's completely out of bounds, every incendiary glance tempts her to break the palace's rules ... Neither of them can risk the scandal that being publicly involved could cause, but the allure of a secret fling is impossible to resist. After all, what's the harm in some short-term fun? Yet, when she's wrapped in Mateo's strong arms, temporary is the last thing on Jessica's mind...